Hip fracture incidence in Japan: Estimates of new patients in 2012 and 25-year trends. Issue 5 (May 2016) - Orimo, H.; Yaegashi, Y.; Hosoi, T.; Fukushima, Y.; Onoda, T.; Hashimoto, T.; Sakata, K.
Abstract Summary We estimated the number of hip fracture patients in 2012 in Japan and investigated the trends in incidence during a 25-year period from 1987 to 2012. Despite the increasing number of patients, the incidence of hip fracture in both men and women aged 70–79 years showed the possibility of decline. Introduction The objectives of this study were to estimate the number of hip fracture patients in 2012, to investigate the trends in incidence during a 25-year period from 1987 to 2012, and to determine the regional differences in Japan. Methods Data were collected through a nationwide survey based on hospitals by a mail-in survey. Hip fracture incidences by sex and age and standardized incidence ratios by region were calculated. Results The estimated numbers of new hip fracture patients in 2012 were 175, 700 in total (95 % CI 170, 300–181, 100), 37, 600 (36, 600–38, 600) for men and 138, 100 (134, 300–141, 900) for women. The incidence rates in both men and women aged 70–79 years were the lowest in the 20-year period from 1992 to 2012. The incidence was higher in western areas of Japan than that in eastern areas in both men and women; however, the difference in the incidence of hip fracture between western and eastern areas is becoming smaller. Conclusions Despite the increasing number of new patients, the incidence of hip fracture in both men and women aged 70–79 years showed the possibility of decline. The exact reasons for this are unknown, but various drugs for improving bone mineral density or preventing hip fracture might have influenced the results. A decrease in the differences in nutrient intake levels might explain some of the change in regional differences in Japan.